Dual Effect of Cyanidin on RANKL‐Induced Differentiation and Fusion of Osteoclasts. Issue 3 (March 2016) - Dou, Ce; Li, Jianmei; Kang, Fei; Cao, Zhen; Yang, Xiaochao; Jiang, Hong; Yang, Bo; Xiang, Junyu; Xu, Jianzhong; Dong, Shiwu
Abstract : Bone homeostasis is maintained by the balance between osteoblastic bone formation and osteoclastic bone resorption. Osteoclasts are multinucleated cells derived from hematopoietic stem cells (HSCs) or monocyte/macrophage progenitor cells and formed by osteoclasts precursors (OCPs) fusion. Cyanidin is an anthocyanin widely distributed in food diet with novel antioxidant activity. However, the effect of cyanidin on osteoclasts is still unknown. We investigated the effect of cyanidin on RANKL‐induced osteoclasts differentiation and cell fusion. The results showed that cyanidin had a dual effect on RANKL‐induced osteoclastogenesis. Lower dosage of cyanidin (< 1µg/ml) has a promoting effect on osteoclastogenesis while higher dosage of cyanidin (> 10µg/ml) has an inhibitory effect. Fusogenic genes like CD9, ATP6v0d2, DC‐STAMP, OC‐STAMP, and osteoclasts related genes like NFATc1, mitf, and c‐fos were all regulated by cyanidin consistent to its dual effect. Further exploration showed that low concentration of cyanidin could increase osteoclasts fusion whereas higher dosage of cyanidin lead to the increase of LXR‐β expression and activation which is suppressive to osteoclasts differentiaton. All these results showed that cyanidin exhibits therapeutic potential in prevention of osteoclasts related bone disorders. J. Cell. Physiol. 231: 558–567, 2016. © 2014 Wiley Periodicals, Inc.